Pengaruh Kejelasan Sasaran Anggaran, Pengendalian Akuntansi Terhadap Laporan Akuntabilitas Kinerja Instansi Pemerintah (LAKIP) Daerah Kabupaten Ogan Komering Ulu (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The objectives to be achieved in this study were to determine the effect of clarity of budget targets, accounting control on the OKU District Government Agency Performance Accountability report. The analytical method used is a quantitative method using multiple linear regression analysis tools. From the results of this study it can be concluded that, partially there is a significant effect of clarity of budget targets on the Performance Accountability of Local Government Agencies of OKU Regency, and there is no significant effect of accounting control on the Performance Accountability of Local Government Agencies of OKU Regency. The contribution of the clarity of budget objectives, accounting control on Performance Accountability was 36.8%, while the remaining 63.2% was influenced by other variables not included in this research model.